2009
DOI: 10.1007/s00018-009-8712-7
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of cullin-RING E3 ubiquitin-ligases by neddylation and dimerization

Abstract: Cullin-RING E3 ubiquitin-Ligases (CRLs) are the most prominent class of ubiquitin-ligases. By controlling the stability of a cohort of key regulators, CRLs impinge on many cellular and biological processes such as immunity, development, transcription, cell signalling and cell cycle progression. CRLs are multi-subunit complexes composed of a catalytic site and a substrate recognition module nucleated around a cullin scaffold protein. Most eukaryotic genomes encode at least five distinct cullins, and each of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
174
0
4

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(183 citation statements)
references
References 140 publications
5
174
0
4
Order By: Relevance
“…6C, left and middle panels). Several previous studies have also shown that CRLs take dynamic conformations (35,36), the flexibility of which may be rate-limiting for ligase activity. Dimerizations of substrate recognition proteins may influence the positioning of the substrate within the complex, as suggested by the analysis of the F-box protein Cdc4.…”
Section: Discussionmentioning
confidence: 96%
“…6C, left and middle panels). Several previous studies have also shown that CRLs take dynamic conformations (35,36), the flexibility of which may be rate-limiting for ligase activity. Dimerizations of substrate recognition proteins may influence the positioning of the substrate within the complex, as suggested by the analysis of the F-box protein Cdc4.…”
Section: Discussionmentioning
confidence: 96%
“…One of the recovered interactors, which encodes the full length of Nedd8 protein, attracted our attention for two reasons. First, neddylation has been well defined as an essential activation mechanism of Cullin-RING E3s 4 . The relationship between neddylation and HECT E3s has not been studied.…”
Section: Nedd8 Correlates With Smurf1 Expression In Colorectal Cancermentioning
confidence: 99%
“…In contrast, RING E3s are scaffolds that recruit E2 to the substrate to facilitate the direct transfer of ubiquitin 1 . Cullin-RING ligases (CRLs) are the most prominent class of E3s and play a pivotal role in the regulation of immunity, development, cell signalling and cell cycle 3,4 . Modification of CRLs by the ubiquitin-like Nedd8 (neural precursor cell-expressed developmentally downregulated protein 8), called neddylation, has been demonstrated to be essential for their activation 1,5 .…”
mentioning
confidence: 99%
“…Although a Ub chain is the preferred binding partner of these shuttle proteins, monoubiquitin (monoUb) has been shown to interact with them as well, albeit with lower affinity (58 -62). Moreover, as Rub1 is documented to form monomeric modifications on its targets (26,28), comparison of its binding preferences with monoUb might unlock a clue as to what distinguishes the two. To assess whether Rub1 interacts with the UBA domains of these receptors, 15 N labeled Rub1 was titrated with the UBA domains of hHR23a, human UQ1, and yeast Ddi1, and the interaction was monitored using NMR spectroscopy (see Fig.…”
Section: Rub1 Is Structurally Similar To Ubiquitin-although Rub1 Ismentioning
confidence: 99%
“…In contrast, the Rub1 pathway exclusively attaches monomeric Rub1 to substrates and performs mainly regulatory functions (26). The attachment of Rub1 (rubylation) to cullin proteins and the subsequent regulation of a multi-subunit E3 ligase, the Skp, cullin, and F-box containing complex, is probably the most prevalent, and clearly the best studied, biological function reported so far (22,23,27,28). However, some other proteins have recently been shown to be modified by Nedd8, including p53 and its E3 ligase Mdm2 (29 -31), p73 (a homolog of p53) (32), ribosomal protein L11 (33,34), epidermal growth factor receptor (EGFR) (35), caspase-7 (36,37), and parkin (38,39), though the effects are still vague, particularly as the ratio of modified to unmodified forms of each protein is extremely low.…”
mentioning
confidence: 99%